In situ growth of large-area and self-aligned graphene nanoribbon arrays on liquid metal. Issue 12 (16th December 2020) - Cai, Le; He, Wanzhen; Xue, Xudong; Huang, Jianyao; Zhou, Ke; Zhou, Xiahong; Xu, Zhiping; Yu, Gui
Abstract: Intrinsic graphene features semi-metallic characteristics that limit its applications in electronic devices, whereas graphene nanoribbons (GNRs) are promising semiconductors because of their bandgap-opening feature. However, the controllable mass-fabrication of high-quality GNR arrays remains a major challenge. In particular, the in situ growth of GNR arrays through template-free chemical vapor deposition (CVD) has not been realized. Herein, we report a template-free CVD strategy to grow large-area, high-quality and self-aligned GNR arrays on liquid copper surface. The width of as-grown GNR could be optimized to sub-10 nm with aspect ratio up to 387, which is higher than those of reported CVD-GNRs. The study of the growth mechanism indicates that a unique comb-like etching-regulated growth process caused by a trace hydrogen flow guides the formation of the mass-produced self-aligned GNR arrays. Our approach is operationally simple and efficient, offering an assurance for the use of GNR arrays in integrated circuits. Abstract : A comb-like etched patterns triggered by the trace hydrogen flow was used to in-situ grow large-area and self-aligned graphene nanoribbon arrays on liquid copper.